Household Transmission of Carbapenemase-producing Enterobacterales in Ontario, Canada. (1st September 2020) - Jamal, Alainna J; Faheem, Amna; Farooqi, Lubna; Zhong, Xi Zoe; Armstrong, Irene; Boyd, David A; Borgundvaag, Emily; Coleman, Brenda L; Green, Karen; Jayasinghe, Kithsiri; Johnstone, Jennie; Katz, Kevin; et al.
Abstract: Background: Data on household transmission of carbapenemase-producing Enterobacterales (CPE) remain limited. We studied risk of CPE household co-colonization and transmission in Ontario, Canada. Methods: We enrolled CPE index cases (identified via population-based surveillance from January 2015 to October 2018) and their household contacts. At months 0, 3, 6, 9, and 12, participants provided rectal and groin swabs. Swabs were cultured for CPE until September 2017, when direct polymerase chain reaction (PCR; with culture of specimens if a carbapenemase gene was detected) replaced culture. CPE risk factor data were collected by interview and combined with isolate whole-genome sequencing to determine likelihood of household transmission. Risk factors for household contact colonization were explored using a multivariable logistic regression model with generalized estimating equations. Results: Ninety-five households with 177 household contacts participated. Sixteen (9%) household contacts in 16 (17%) households were CPE-colonized. Household transmission was confirmed in 3/177 (2%) cases, probable in 2/177 (1%), possible in 9/177 (5%), and unlikely in 2/177 (1%). Household contacts were more likely to be colonized if they were the index case's spouse (odds ratio [OR], 6.17; 95% confidence interval [CI], 1.05–36.35), if their index case remained CPE-colonized at household enrollment (OR, 7.00; 95% CI, 1.92–25.49), or if they had at least 1 set of specimens processed after direct PCR was introduced (OR, 6.46; 95% CI, 1.52–27.40). Conclusions: Nine percent of household contacts were CPE-colonized; 3% were a result of household transmission. Hospitals may consider admission screening for patients known to have CPE-colonized household contacts. Abstract : This prospective cohort study of 95 carbapenemase-producing Enterobacterales (CPE) index cases and 177 household contacts detected 9% of household contacts as CPE-colonized; 3% were due to confirmed/probable household transmission. Hospital admission screening programs may consider including household contacts of known CPE cases.